(untitled) (Revista Científica Integrada, 2023)
Aim: To carry out a survey on the prevalence of gestational and congenital syphilis in the world context, and to identify the associated risk factors. Methods: An integrative review, was conducted in three databases (PubMed, EMBASE, and Web of Science), using the terms “Pregnant” or “Pregnant woman”, “Risk Factors”, “Prevalence” and “Syphilis”. The studies should be in line with the study’s objectives, be observational, and be published in the last five years. Results: Of the 162 papers identified, only 20 made up the final sample. Of these, 65% were developed on the African continent. The prevalence of gestational syphilis ranged from 0.6% to 56.4% between 2009 and 2021. The most common risk factors were low education, age over 35, drug use, and a history of sexually transmitted infections. Conclusion: Prevalence data are heterogeneous and distinct, depending on the region of the globe. However, risk factors are close and valuable for better tracking of cases and investments in health.